Negative Influence of Insufficient Sleep on Endothelial Vasodilator and Fibrinolytic Function in Hypertensive Adults. Issue 6 (7th September 2021) - Stockelman, Kelly A.; Bain, Anthony R.; Goulding, Anabel; DeSouza, Noah M.; Rahaman, Clay; Maly, Lukas; Greiner, Jared J.; Stauffer, Brian L.; DeSouza, Christopher A.
Abstract : Insufficient nightly sleep (<7 hour/night) has been linked to the cause of hypertension and is a prevalent, often ignored, comorbidity. We tested the hypotheses that chronic nightly insufficient sleep is associated with lower nitric oxide-mediated endothelium-dependent vasodilation and endothelial tPA (tissue-type plasminogen activator) release in hypertensive adults; and that the insufficient sleep-related reduction in endothelial vasodilator and fibrinolytic function is due to increased oxidative stress. Fifty hypertensive adults were studied: 20 with normal nightly sleep duration (14M/6F; age: 59±2 year; blood pressure: 138/83±1/1 mm Hg; sleep: 7.6±0.1 hour/night) and 30 with short nightly sleep duration (21M/9F; 56±1 year; 138/84±2/1 mm Hg; 5.8±0.1 hour/night). Forearm blood flow (plethysmography) was determined in response to intraarterial infusion of: acetylcholine in the absence and presence of N G -monomethyl-L-arginine and the antioxidant vitamin C; bradykinin in the absence and presence of vitamin C; and sodium nitroprusside. Endothelial release of tPA was determined in response to bradykinin without and with vitamin C. Vasodilation to acetylcholine was significantly lower (≈20%) in the short versus normal sleep adults. N G -monomethyl-L-arginine reduced (≈25%; P <0.05) acetylcholine vasodilation in the normal but not short sleepers. Vitamin C increased (≈35%; P <0.05) acetylcholine vasodilation in short sleepers only. Endothelial tPA release to bradykinin was significantly lower (≈25%) in the short versus normal sleep duration adults. Co-infusion of vitamin C induced greater tPA release in short sleepers. In hypertensive adults, insufficient sleep is associated with reduced nitric oxide–mediated endothelium-dependent vasodilation and endothelial tPA release. These sleep-related abnormalities in endothelial function are due, in part, to oxidative stress.